Self Empowerment in Patient with Chronic Disease: A Literature Review - Evi Nursyafitri; Wantiyah Wantiyah; Jon Hafan Sutawardana (NurseLine Journal, 2021)
Bacground: Chronic disease is the highest cause of death in the world and Indonesia which can affect patient’s quality of life. One of the key factors for a good patient’s quality of life is empowerment. Self-empowerment is important for patients in making decisions with health professionals regarding the patient's health. Purpose: The aim study was to explore self empowerment in patient with chronic disease. Methods: The methods was a narrative literature. Selection of articles using PRISMA flow diagram. The databases used Science Direct, Pubmed, and Google Scholar. Result: The result was 5 articles discuss empowerment and 6 articles discuss intervention related to empowerment. Empowerment develops while increasing self-efficacy and self-management. Empowerment can also improve the relationship between patients and health professionals. As for interventions related to empowerment, including health education, empowerment based on experiential learning, energy conservation, mobile health technology. Conclussion: Patients with chronic disease have a responsibility in managing their disease. Therefore, empowerment becomes important in patients with chronic disease. In addition, empowerment can also improve health outcomes. An effective intervention in increasing empowerment is to provide health education to patients and families about the illness.